2007
DOI: 10.1111/j.1439-0523.2007.01338.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of protein, starch and oil content of single intact kernels by near infrared reflectance spectroscopy (NIRS) in maize (Zea mays L.)

Abstract: Maize samples (n ¼ 309) containing 3090 single intact kernels from a broad variety of breeding materials were scanned by Near Infrared Reflectance Spectroscopy (NIRS) to develop non-destructive determination calibrations for crude protein, starch and oil content in kernels. Calibration equations of single kernels were developed by partial least square regression (PLS). Regression parameters between the chemical values, determined by reference methods, and the predicted values, determined by Near Infrared Refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 5 publications
3
30
0
1
Order By: Relevance
“…Studies about this subject in the literature show similar results (r=0.98 for PLSR, r=0.97 for MLR) with regards to the evaluation parameters of PLSR and MLR models for the estimation of protein content (Orman & Schumann 1991). Contemporary literature contains some reports regarding the estimation of protein ratio in maize grain by NIRS (Baye et al 2006;Jiang et al 2007;Spielbauer et al 2009;Tallada et al 2009). Our models had relatively higher estimation powers than the models in those studies; however, it would not be appropriate to make such a comparison because intact grain material were used there as opposed to ground material in our study, and the NIR instruments used were quite different.…”
Section: Comparison and Evaluation Of Calibration Modelssupporting
confidence: 51%
“…Studies about this subject in the literature show similar results (r=0.98 for PLSR, r=0.97 for MLR) with regards to the evaluation parameters of PLSR and MLR models for the estimation of protein content (Orman & Schumann 1991). Contemporary literature contains some reports regarding the estimation of protein ratio in maize grain by NIRS (Baye et al 2006;Jiang et al 2007;Spielbauer et al 2009;Tallada et al 2009). Our models had relatively higher estimation powers than the models in those studies; however, it would not be appropriate to make such a comparison because intact grain material were used there as opposed to ground material in our study, and the NIR instruments used were quite different.…”
Section: Comparison and Evaluation Of Calibration Modelssupporting
confidence: 51%
“…However, NIRS has been used in several applications for single seed analysis with notable success. Quantitative applications in single corn kernels are mainly targeting oil content (Cogdill et al, 2004;Janni et al, 2008;Jiang et al, 2007;Orman and Schumann, 1992;Spielbauer et al, 2009;Weinstock et al, 2006), protein levels (Spielbauer et al, 2009), moisture calibrations (Armstrong, 2006;Finney and Norris, 1978), and starch (Spielbauer et al, 2009). The predictive ability of those calibrations indicated that NIRS is a suitable technology for screening organic compounds in single corn kernels.…”
Section: Introductionmentioning
confidence: 99%
“…The variety Crioulo Oito Carreiras nº 41 had the higher protein level (12.41%), whereas the variety Caiano Rajado nº16 had the lower (10.26 %). In the literature some authors reported that the protein contents for corn landraces were between 10.47 to 12.17 % (Câmara, 2005), and in hybrids from 7.77 to 13.84 % (Jiang et al, 2007). The average value found for dietary fiber was of 13.0 % and for starch this value was of 60.54 %.…”
Section: Resultsmentioning
confidence: 96%